Religious Moderation in Yogyakarta Madrasahs: An Evaluation Study - M. Abzar Duraesa; Anggie Nadia Dinihari (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
Discrimination and extremism undermine social cohesion, emphasizing the need for character education especially religious moderation in madrasah curricula. However, Society 5.0's learning needs necessitate higher-order thinking teaching methods like Computational Thinking. To address Society 5.0 challenges, this study evaluates a religious moderation program integrated into Islamic education materials using computational thinking (CT). This qualitative descriptive study focused on context, transactions, and outcomes using Stake's Countenance evaluation paradigm. 112 professors and 1,276 students were interviewed at Yogyakarta Special Region madrasahs. To keep the trustworthiness, we interviewed and coded and checked the data again. The earlier review shows that program preparation and requirements met Ministry of Religious Affairs objectives, including teacher aid to internalize religious moderation through CT-oriented instruction. Classroom learning and school culture activities like Islamic education recitals and Rohis demonstrate the program's implementation, according to the transaction evaluation. The outcome review shows that coaching, workshops, and training sessions on religious moderation and critical thinking continue throughout school hours, disrupting learning. Criticism as a digital-era competency and a comprehensive educational framework for religious moderation in Islamic education improves academic discourse. It adapts Stake's Countenance concept to madrasah values education. It provides empirical evidence from a large participant cohort on policy criteria translation into everyday learning. It finds a real-world governance gap””training scheduling””that can reduce program effectiveness even in ready contexts. Program managers can use it to link character education goals to instructional time. It also proposes evaluating other places that desire to combine CT with religious moderation. Finally, it links cognitive talents to social and ethical resilience in schooling to boost Society 5.0 discussions.